Tree diversity and soil fertility interactions drive carbon storage in degraded cocoa landscapes of Côte d’Ivoire - Atangana, Alain R.; Kouassi Koffi, Guillaume; Kpangui, Kouassi Bruno; Tondoh, Ebagnerin Jerôme; Wolf, Valentin L. F.; Kouamé, Christophe; Khasa, Damase (Frontiers in Plant Science, 2025)
IntroductionUnderstanding the ecological functioning of degraded cocoa landscapes is critical for restoring productivity and ecosystem services in West Africa. This study investigated how climate, geography, and land-use systems interact to shape tree diversity, soil fertility, and aboveground carbon (AGC) stocks across six cocoa-producing sites in Côte d’Ivoire.MethodsField inventories and soil sampling to 50 cm depth were conducted across gradients of climate (1,150–1,650 mm rainfall) and land-use systems (fallow, cocoa agroforestry, and monocropping). Mixed effects ANOVA, regression, and redundancy analyses were applied to test three hypotheses linking environmental gradients, tree diversity, and soil–carbon relationships.ResultsLand-use system had the strongest effect on tree diversity (P< 0.0001), with fallows supporting significantly higher richness (7.2 ± 0.51) and Shannon diversity (1.7 ± 0.05) than agroforestry or monocrop systems. Climate and site nested within climate also significantly influenced species abundance and evenness. Soil fertility indicators were primarily controlled by climate and geographic site, with significant effects on pH, exchangeable bases, and structural stability. Interactions between climate and land-use significantly affected soil pH, organic carbon, calcium, and cation exchange capacity. Stepwise regression identified aluminum, potassium, boron, and magnesium as key soil predictors of AGC (R² = 0.14; P< 0.0001), while species richness was the only diversity metric significantly associated with AGC (R² = 0.12; P< 0.0001).DiscussionThese results highlight the dominant role of species richness over evenness and abundance in sustaining soil fertility and carbon storage, emphasizing biodiversity conservation as a cornerstone of cocoa landscape restoration.